2023
DOI: 10.3389/fped.2023.1157630
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequencing has a high diagnostic yield in children with congenital anomalies of the heart and urinary system

Abstract: BackgroundCongenital heart defects (CHD) and congenital anomalies of the kidney and urinary tract (CAKUT) account for significant morbidity and mortality in childhood. Dozens of monogenic causes of anomalies in each organ system have been identified. However, even though 30% of CHD patients also have a CAKUT and both organs arise from the lateral mesoderm, there is sparse overlap of the genes implicated in the congenital anomalies for these organ systems. We sought to determine whether patients with both CAKUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For infants requiring early surgical intervention, studies have shown that positive genetic testing results have been associated with post-operative complications and survival and can impact care and resource utilization [ 16 , 41 , 42 , 43 , 44 , 45 ]. Cohort studies have demonstrated that genetic testing of newborns with CHD yields an overall diagnostic rate of ~30% with genome-wide analysis [ 46 , 47 , 48 , 49 , 50 ]. The testing yield is slightly higher in cases of CHD with extra-cardiac anomalies, but results are still robust when the CHD is isolated [ 51 , 52 ].…”
Section: Postnatal Genetic Testing In Chdmentioning
confidence: 99%
“…For infants requiring early surgical intervention, studies have shown that positive genetic testing results have been associated with post-operative complications and survival and can impact care and resource utilization [ 16 , 41 , 42 , 43 , 44 , 45 ]. Cohort studies have demonstrated that genetic testing of newborns with CHD yields an overall diagnostic rate of ~30% with genome-wide analysis [ 46 , 47 , 48 , 49 , 50 ]. The testing yield is slightly higher in cases of CHD with extra-cardiac anomalies, but results are still robust when the CHD is isolated [ 51 , 52 ].…”
Section: Postnatal Genetic Testing In Chdmentioning
confidence: 99%